Polish Street Namesakes. General Characteristics and Preliminary Outline for Analysing Urban Space Names - Rutkowski, Mariusz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The article addresses the issue of commemorative street names as carriers of memory and signs of national identity. The overall collection of Polish streets, gathered in the TERYT database of the Central Statistical Office, is taken into consideration. The specificity of commemorative names and the essence of commemoration as a social phenomenon are discussed. The article presents a list of the 100 most common street namesakes in Poland, along with their most general characteristics (typology of namesakes) linked to numerical data. The final section sketchily outlines the research potential based on such a database, focused on unveiling significant aspects of Polish culture and value patterns.